PENGARUH PENGHINDARAN PAJAK, BIAYA MODAL EKUITAS, DAN TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN CSR - Rizqiyah, Anggraini Nawal; Lating, Ade Irma Suryani; Muflihin , Mohammad Dliyaul (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
A fundamental aspect of conducting business is to ensure that a company’s operations are consistent with social standards and community expectations in order to secure social acceptance. To achieve this, organizations often adopt non-financial communication approaches, including the publication of corporate social responsibility (CSR) reports. This study seeks to analyze the effect of tax avoidance, cost of equity, and corporate governance mechanisms particularly family and foreign ownership on CSR disclosure. The research is based on a sample of 50 mining firms listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023, chosen through a purposive sampling technique. The data were processed using panel data regression with the aid of EViews version 12.The results demonstrate that tax avoidance has a significant negative impact on CSR disclosure, while cost of equity, family ownership, and foreign ownership do not show a meaningful influence. These findings suggest that, although tax avoidance tends to reduce corporate social transparency, the ownership composition and shareholder value are not the primary determinants of CSR reporting in the mining sector.